Disseminated Penicillium marneffei infection in human immunodeficiency virus-infected children - Sirisanthana V. (2014)
Disseminated infection with the fungus Penicillium marneffei is one of the most common opportunistic infections in human immunodeficiency virus (HIV) disease in northern Thailand. We report the clinical, laboratory and therapeutic features of 21 human immunodeficiency virus-infected children with disseminated P. marneffei who were prospectively followed. Significant clinical and laboratory features included generalized lymphadenopathy (90%), hepatomegaly (90%), body temperature > 38.5 degrees C (81%), papular skin lesions with central umbilication (67%), splenomegaly (67%), failure to thrive (52%), severe anemia (hemoglobin < 60 g/liter) (43%) and thrombocytopenia (platelet count < 0.5 x 10(11)/liter) (21%). The response rate in patients who were treated with appropriate antifungal therapy (amphotericin B, fluconazole or ketoconazole) was 82%. No relapse was observed in patients given ketoconazole prophylactically. Skin lesions, usually papules with central necrotic umbilication, provide the most significant clue to the diagnosis. Early diagnosis based on finding P. marneffei in the skin smear or lymph node provides the basis for prompt administration of antifungal therapy and improved outcome.